1987
DOI: 10.21273/jashs.112.3.441
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Apple Rootstocks and Nematicides on Pratylenchus penetrans Populations and Apple Tree Growth

Abstract: ‘Rogers Red McIntosh’ (Malus domestica Borkh.) on Mailing Merton (MM)111, MM 106, Mailing (M) 26 and M 7a were planted within an old apple orchard site. The trees were trickle-irrigated and the sandy soil was treated with the nematicides Telone (C-17), Vorlex, or Nemacur 3. In 1984, data were collected from trees excavated at 50, 100, and 156 days after planting and from permanent trees in 1985 from plots treated with nematicides prior to planting. The numbers of Pratylenchus penetrans [(Cobb) Filipjev & S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…The fieldwide FS : PS dry weight ratio was 0.44, indicating a significant (P < 0.0001) increase in seedling growth following soil pasteurization. These observations were consistent with prior studies of nematoderelated replant problems (Mai and Abawi, 1978;Costante et al, 1987;Hoestra, 1968). Soil pasteurization with steam (70C for 35 min) has consistently eradicated phytonematodes and also suppressed pathogenic fungi and non-spore-forming bacteria (Mulder, 1979).…”
Section: Resultssupporting
confidence: 92%
“…The fieldwide FS : PS dry weight ratio was 0.44, indicating a significant (P < 0.0001) increase in seedling growth following soil pasteurization. These observations were consistent with prior studies of nematoderelated replant problems (Mai and Abawi, 1978;Costante et al, 1987;Hoestra, 1968). Soil pasteurization with steam (70C for 35 min) has consistently eradicated phytonematodes and also suppressed pathogenic fungi and non-spore-forming bacteria (Mulder, 1979).…”
Section: Resultssupporting
confidence: 92%
“…Recent studies in Washington State have shown that the use of SM in combination with certain rootstocks (e.g., Geneva V R series rootstocks) can significantly alter soil microbiome and the rhizosphere community to mitigate apple replant disease (Mazzola et al, 2009(Mazzola et al, , 2015Mazzola, 2019a, 2019b). A recent field trial in north-central Washington State focused on identifying the effects of the interaction among four soil treatments [2.2, 4.4, and 6.6 t per hectare (t•ha À1 ) SM, and a traditional fumigant] and a no treatment control with two rootstock genotypes, 'M.26' [ARD susceptible (Costante et al, 1987Reim et al, 2019] and 'Geneva 41' ['G.41', ARD tolerant (Isutsa and Merwin, 2000;Reim et al, 2019;Robinson et al, 2011)] on the soil microbiome community as it related to ARD (Wang and Mazzola, 2019a). In addition to effects on the soil microbiome, differences in tree growth, tree mortality, and crop yields were observed among soil treatments and rootstock genotype comparisons (Wang and Mazzola, 2019a).…”
mentioning
confidence: 99%